2012
DOI: 10.1097/psy.0b013e31825904eb
|View full text |Cite
|
Sign up to set email alerts
|

Insomnia and High-Sensitivity C-Reactive Protein

Abstract: There were no consistent associations between symptoms of insomnia and hsCRP levels. Our results do not support the hypothesis that inflammation, as reflected by elevated levels of hsCRP, is an important factor linking insomnia to coronary heart disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
28
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 53 publications
5
28
0
1
Order By: Relevance
“…Inflammatory processes are assumed to represent an important biological mechanism linking poor sleep to cardiovascular disease [4], [5]. Although experimental studies clearly indicated that sleep deprivation and insomnia can increase inflammatory processes, the relationships of sleep with inflammation remain far from being settled [4].…”
Section: Introductionmentioning
confidence: 99%
“…Inflammatory processes are assumed to represent an important biological mechanism linking poor sleep to cardiovascular disease [4], [5]. Although experimental studies clearly indicated that sleep deprivation and insomnia can increase inflammatory processes, the relationships of sleep with inflammation remain far from being settled [4].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have identified an independent association between sleep characteristics (namely, disordered breathing, duration, and quality ratings) and inflammation (22-33). Other studies have reported that associations between these sleep characteristics and inflammation are accounted for by confounders like disease and adiposity (34-39)). However, previous literature on sleep and inflammation has been limited by sample size and/or reliance upon subjective measures of sleep.…”
mentioning
confidence: 98%
“…The current report therefore aimed to determine whether objectively measured sleep characteristics are associated with mortality risk independent of concurrent inflammation. Several factors other than sleep may also be associated with inflammation and mortality, and the relationship between sleep and inflammatory markers may be confounded by factors like adiposity and overt disease (34-39). Therefore, we assessed the relative roles of inflammatory burden and other health factors (that may be related to sleep, inflammation, and mortality (e.g.…”
mentioning
confidence: 99%
“…It has been proposed that people with insomnia have physiologic hyperarousal as evidenced by greater nighttime resting HR, 23,24 central and sympathetic nervous system dysregulation, 23,25-29 heightened hypothalamic-pituitary adrenal axis activation, 30-32 and greater nighttime whole-body metabolism. 33 Other, but not all, 34 studies reported a relationship between insomnia symptoms and higher levels of inflammatory markers (IL-6, 35-37 CRP 37,38 ) compared to good sleepers. In our study we did not find that daytime resting heart rate or CRP differed between people with symptoms of insomnia or good sleepers.…”
Section: Discussionmentioning
confidence: 99%